Assuming the pattern would continue: 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, 15, 14, 13...
If you mean: 6 12 18 24 then the nth term is 6n
(23 + 25)/(24 - 22) = 48/2 = 24
1 + 1 + 22 = 24
Well, darling, the nth term for the sequence 18, 12, 6, 0, -6 is -6n + 24. So, if you plug in n = 1, you get 18; n = 2 gives you 12, and so on. Just a little math magic for you to enjoy!
If you mean: 34 39 24 ... then the nth term is 39-5n and so the 100th term = -461
The nth term is (36 - 4n)
If you mean: 6 12 18 24 then the nth term is 6n
24-5n
It goes up by (24-16) = 8 each time. The first time is 16. So the nth term is 8n + 8.
44
Give the simple formula for the nth term of the following arithmetic sequence. Your answer will be of the form an + b.12, 16, 20, 24, 28, ...
(23 + 25)/(24 - 22) = 48/2 = 24
If 3 is the first term, then the nth term is [ 3 x 2(n-1) ] .
If 3 is the first term, then the nth term is [ 3 x 2(n-1) ] .
7n - 4
The nth term in the arithmetic progression 10, 17, 25, 31, 38... will be equal to 7n + 3.
1 + 1 + 22 = 24